Effect of different surface treatments on porcelain-resin bond strength - Yavuz, Tevfik; Özyılmaz, Özgün Yusuf; Dilber, Erhan; Tobi, Elif Sümeyye; Kılıç, Hamdi Şükür (Wiley, 2017)
Purpose:The aim of this study was to evaluate the effects of various surface treatments on the surface structure and shear bond strength (SBS) of different ceramics. Materials and Methods: total of 192 disk-shaped cores were prepared using two all-ceramic systems, of which 168 were submitted to SBS tests, and 24 were investigated by scanning electron microscopy (SEM) and atomic force microscopy (AFM). The ceramics used were IPS Empress e.max (EX) lithium glass-ceramic and Vita In-Ceram Zirconia glass-infiltrated zirconia (ICZ). The specimens were randomly divided into seven groups (n = 12) on the basis of the surface treatment used: control; SB-sandblasting with 50 mu m Al2O3 particles; CJ-chairside silica coating with 30 mu m SiO2 particles and silanization (Clearfil Porcelain Bond Activator); HF-etching in 5% hydrofluoric acid and silanization; ER-etching with an Er:YAG laser (10 W); ND-Nd:YAG laser etching (0.8 W); and FS-etching with a femtosecond laser (860 mW). A luting cement (Clearfil Esthetic) was photopolymerized on each treated ceramic disk. After subjecting the specimens to thermocycling (1000 cycles, 5 degrees C to 55 degrees C), SBS tests were performed using a universal testing machine. The data were analyzed with two-way ANOVA and Tukey's tests using a significance limit of 5%. Results: ong the EX ceramics, the CJ (29.10 MPa) and HF (26.07 MPa) specimens had statistically higher SBS values. For the ICZ ceramics, the highest value (28.08 MPa) was obtained for the CJ specimens. Conclusions: lanization after coating with silica improves the bond strengths of both EX and ICZ specimens, while HF etching is favorable only for the EX specimens.
WOS: 000405822000015
PubMed ID: 26480029
Keywords: Laser Etching; Silica Coating; Zirconia; Glass-Ceramic